ANALISIS PEMBELAJARAN FISIKA DALAM SISTEM MOVING CLASS DI SMP NEGERI 1 PEKALONGAN LAMPUNG TIMUR TAHUN PELAJARAN 2012/2013 - Hari Pribadi; Purwiro Harjati (Jurnal Pendidikan Fisika, 2014)
The purpose of this study was to determine the level of effectiveness, efficiency and the magnitude of the attraction of students towards learning physics in moving class learning system. This study uses a population of eighth grade students of Junior High School State 1 Pekalongan, then the sample is used to determine the cluster random sampling. Samples are VIII2 grade 27 students who take physics learning on the subject of style. Data was collected through observations, questionnaires, documentation and interview methods. From the analysis it can be concluded that: 1) The level of effectiveness of learning physics in moving class learning system is quite good in the learning process, it show up of learning achievement level showed 46.2% were able to be achieved by all students. 2) The level of efficiency learning physics in moving class learning system can be said to have been good, because of the time in the planning and implementation of learning physics have been as expected. 3) The amount of the attraction of students towards learning physics in moving class system in either category, where there are 58% of students interested while the other 42% claimed not to be interested.